2015
DOI: 10.1089/neu.2014.3530
|View full text |Cite
|
Sign up to set email alerts
|

A Combination Therapy of Nicotinamide and Progesterone Improves Functional Recovery following Traumatic Brain Injury

Abstract: Neuroprotection, recovery of function, and gene expression were evaluated in an animal model of traumatic brain injury (TBI) after a combination treatment of nicotinamide (NAM) and progesterone (Prog). Animals received a cortical contusion injury over the sensorimotor cortex, and were treated with either Vehicle, NAM, Prog, or a NAM/Prog combination for 72 h and compared with a craniotomy only (Sham) group. Animals were assessed in a battery of behavioral, sensory, and both fine and gross motor tasks, and give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…Extending these deficits with the SMC model allows for a more long-term evaluation of any potential strategies of improving recovery of function. This benefit of using the SMC as a target structure for TBI to measure combination therapy treatment has been demonstrated in the literature[47]. However, one benefit to the use of both the bilateral frontal model and the unilateral parietal model is the appearance of MWM deficits several weeks after injury[21, 23, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Extending these deficits with the SMC model allows for a more long-term evaluation of any potential strategies of improving recovery of function. This benefit of using the SMC as a target structure for TBI to measure combination therapy treatment has been demonstrated in the literature[47]. However, one benefit to the use of both the bilateral frontal model and the unilateral parietal model is the appearance of MWM deficits several weeks after injury[21, 23, 27].…”
Section: Discussionmentioning
confidence: 99%
“…PROG has also been shown in numerous studies to confer significant benefits after experimental brain injury (Cutler et al, 2007; Cekic et al, 2009; Cekic and Stein, 2010; Stein and Cekic, 2011). Both treatments work in part by regulating signaling pathways involved in neuroinflammation and as such, Peterson and colleagues (2015) hoped to augment this mechanism by administering these agents alone and in combination, to explore effects on behavioral outcome, lesion volume, neuronal degeneration, and astrocyte activation. To this end, adult male rats received a CCI injury of moderate severity and subsequently received NAM (75 mg/kg loading dose and 12 mg/kg/h infusion thereafter), PROG (75 mg/kg loading dose at 4 h post-injury and 10 mg/kg every 12 h thereafter until sacrifice), their combination, or vehicle.…”
Section: Inflammationmentioning
confidence: 99%
“…Indicating a synergistic effect, the combination treatment was the only group exhibiting a reduction in cortical lesion volume 24 hr after TBI. However, that benefit was lost when lesion volume was again assessed at 29 days (Peterson et al, 2015). Albeit two large Phase III clinical trials evaluating PROG recently concluded with negative results (Stein, 2015), the current studies suggest that perhaps PROG may still be effective if combined with NAM or other therapeutic approaches at appropriate times after TBI.…”
Section: Inflammationmentioning
confidence: 99%
“…19 Briefly, male adult (3.5 month old) rats were designated as surgical shams or experienced unilateral CCI TBI. Injured animals received Prog or NAM monotherapy, the NAM-Prog combination therapy, or only vehicle, for a total of four injured groups, plus shams.…”
Section: Concurrent Targeted Therapy Combination: Probenecid and N-acmentioning
confidence: 99%
“…Another critical challenge in the face of the negative TBI clinical trial results with PROG, 4,5 despite the compelling pre-clinical data supporting PROG use at lower doses, [18][19][20][21] is that it may be more difficult to find support to test whether other doses of PROG might have been more effective 18,19,22 or to evaluate combination therapies using PROG that might provide better salutary effects over PROG monotherapy.…”
mentioning
confidence: 99%